Analisis Peran Dan Strategi Lazismu Kota Medan Terhadap Pemberdayaan UMKM Di Kota Medan - Imam, Chairul; Tarigan, Azhari Akmal (Universitas Muhammadiyah Metro, 2023)
LAZISMU is an Amil Zakat Institution, Infaq, Shadaqah Muhammadiyah Which has a national scale in community empowerment through productive utilization of zakat funds, infaq, waqf, and other philantropic funds from individuals, companies and other agencies. The establisment of LAZISMU aim as a zakat management institution with efficient finance that can be part of the communitys social problem solver. Limited capital, lack of knowledge of technology, and difficulty in marketing products are the problems faced by Micro, Small and Medium Enterprises (MSME) today. The purpose of this study was to determine the role and strategy of LAZISMU in Medan City towards the Empowerment of MSME in Medan City. This research process uses descriptive qualitative research. Information in this study is based on primary sources. Data collection techniques in this study are through library research and field research. The results of research aimed at LAZISMU Medan City show the results of empowering zakat, infaq, shadaqah funds distributed through two classifications, namely productive and comsumptive.